2021
DOI: 10.1007/s10549-020-06076-5
|View full text |Cite
|
Sign up to set email alerts
|

Real-world data on neoadjuvant endocrine therapy in ER-positive/HER2-negative breast cancer

Abstract: Purpose Neoadjuvant endocrine therapy (NET) has been shown to be effective in ER-positive/HER2-negative breast cancer in clinical trials. However, adoption in clinical practice is still limited. Real-world data may provide useful insights into effectiveness, toxicities and quality of care, potentially rendering clinical trial results to the real-world setting. Our purpose was to report real-world data of a cohort of postmenopausal patients submitted to NET. Methods This prospective cohort study evaluated 146 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Only mild adverse effects were reported, and no treatment abandonment occurred, which is consistent with data from other studies. [23] In conclusion, results from our study indicate that NET can be considered a safe and effective alternative for postmenopausal women with ER+/HER2-breast cancer and that it increases the rates of BCS in both luminal A-like and luminal B-like tumors. Early changes in Ki67 proliferation rates become a feasible and reliable tool that provides crucial information about endocrine responsiveness and patient prognosis.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Only mild adverse effects were reported, and no treatment abandonment occurred, which is consistent with data from other studies. [23] In conclusion, results from our study indicate that NET can be considered a safe and effective alternative for postmenopausal women with ER+/HER2-breast cancer and that it increases the rates of BCS in both luminal A-like and luminal B-like tumors. Early changes in Ki67 proliferation rates become a feasible and reliable tool that provides crucial information about endocrine responsiveness and patient prognosis.…”
Section: Discussionmentioning
confidence: 51%
“…Although randomized NET trials, with or without other drug combinations, are numerous, real-world data, re ecting clinical practice, are scarce in this eld. [23] The aim of this study was to analyze a prospective cohort of patients in our institution who had been treated with NET and subsequently operated on, evaluating the safety (adherence and treatment tolerance) and effectiveness of NET in tumoral downstaging. Furthermore, we wanted to assess the role and clinical applicability of Ki67 changes as an indicator of endocrine responsiveness and, therefore, of NET maintenance.…”
Section: Introductionmentioning
confidence: 99%
“… 27 In addition, some cohort studies also found that NET was well‐tolerated and achieved similar or better effectiveness. 9 , 28 , 29 , 30 Moreover, many studies based on NCDB databases hold the same views and conclusions, such as Kantor, 31 Stafford, 32 Chiba, 33 and Tamirisa. 34 While these studies unanimously support the role of NET in reducing pathological stage, axillary lymph node staging, and increasing BCS rates, they do not analyze the impact of treatment on survival prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that patients with low Ki67 levels respond better to NET. 23 , 29 , 30 , 35 , 36 Prospect traffic reported that pathological response is a favorable prognostic factor following NET. 37 Additionally, other tools such as SET2,3, 38 Oncotype Dx Breast Recurrence Score, 39 and Preoperative Endocrine Prognostic Index (PEPI) 26 have been validated to predict response to endocrine therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive lobular carcinoma accounts for only 15% of breast cancers, but it is known that these are usually especially responsive to NET, even though studies involving this histological subtype are scarce [ 128 ]. Only one “window of opportunity” trial focuses on the characteristics of NET in invasive lobular tumors (NCT02206984), comparing Ki67 changes and ER/PR expression after a 21-day cycle of tamoxifen or anastrozole or two doses of fulvestrant.…”
Section: Ongoing Trialsmentioning
confidence: 99%